UMP celebrates Pahang media practitioners in Iftar Ceremony - Mimi Rabita, Abdul Wahit (2023)
KUANTAN, 28 March 2023 - A total of 100 media practitioners, agency liaison officers and strategic collaboration partners of Universiti Malaysia Pahang (UMP) were celebrated to appreciate the role of the media in improving the visibility of the university while also sharing the latest information.